Inventory of Invasive Alien Plant Species (IAPs) in Bali Botanic Garden and the Adjacent Areas - Farid Kuswantoro; Sutomo Sutomo; Wawan Sujarwo (Jurnal Ilmu Kehutanan)
Similar to other botanic gardens, Bali Botanic Garden (BBG) is also prone to the spread of Invasive Alien Plant (IAP) species. Unfortunately, research about IAP species in BBG is still very limited. Thus, the study aims to update the list of IAP species in BBG and its adjacent areas as well as to provide a garden manager with data of the most important IAP species. This study was conducted by using sampling plots that were purposively established in three areas of BBG, namely the Ekor Burung (EB), VIP, and Kepala Burung (KB). Data analysis was performed to calculate the Relative Frequency (RF), Important Value Index (IVI), Clustering analysis, and NMDS ordination. The study was able to document 18 IAP species. Ageratina riparia and Bidens pilosa have the highest RF in EB, while the former also has the highest RF in VIP and KB. Similarly, the highest IVI was acquired by A. riparia in VIP and KB, as well as by Sida rhombifolia in EB. Cluster analysis revealed two subsets. NMDS ordination suggested that VIP and KB have more similar IAPs than the EB. This study suggested that A. riparia is the most important IAP species in BBG and its surrounding areas.